Paris for one and other stories - Moyes, Jojo 1969- (New York : Penguin Books, 2016)
"Quintessential Jojo Moyes, Paris for One and Other Stories is an irresistibly romantic collection filled with humor and heart. Nell is twenty-six and has never been to Paris. She's never even been on a romantic weekend away--to anywhere--before. Everyone knows traveling abroad isn't really her thing. But when Nell's boyfriend fails to show up for their romantic mini-vacation, she has the opportunity to prove everyone--including herself--wrong. Alone and in Paris, Nell uncovers a version of herself she never knew existed: independent and intrepid. Could this turn out to be the most adventurous weekend of her life?"--
Keywords: Young women -- Fiction; Women -- Fiction; Women; Young women; Paris (France) -- Fiction; France -- Paris; Fiction; Short stories; Short stories; Fiction